2015
DOI: 10.1016/j.chb.2014.11.100
|View full text |Cite
|
Sign up to set email alerts
|

Emotions ontology for collaborative modelling and learning of emotional responses

Abstract: a b s t r a c tEmotions-aware applications are getting a lot of attention as a way to improve the user experience, and also thanks to increasingly affordable Brain-Computer Interfaces (BCI). Thus, projects collecting emotionrelated data are proliferating, like social networks sentiment analysis or tracking students' engagement to reduce Massive Online Open Courses (MOOCs) drop out rates. All them require a common way to represent emotions so it can be more easily integrated, shared and reused by applications i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 21 publications
0
22
0
6
Order By: Relevance
“…These proposed systems aim to explore or improve EEG-based emotion recognition systems. [2,39,41,42,49,50,57,61,63,92,104,108,109,117,131,136,149,152,157,173,174,185,186,189,191,[195][196][197][198][199][200][201][202][203][204][205][206][207][208][209]217,219,[223][224][225]229,[262][263][264][265][266]<...>…”
Section: Monitoringmentioning
confidence: 99%
“…These proposed systems aim to explore or improve EEG-based emotion recognition systems. [2,39,41,42,49,50,57,61,63,92,104,108,109,117,131,136,149,152,157,173,174,185,186,189,191,[195][196][197][198][199][200][201][202][203][204][205][206][207][208][209]217,219,[223][224][225]229,[262][263][264][265][266]<...>…”
Section: Monitoringmentioning
confidence: 99%
“…Sentiment classification of those valuable forum posts can assist instructors to make interventions and guiding instructions to improve learning performance. Lacking monitoring on learners' sentiments may lead to high dropout rates of courses [5]. Moreover, the forum posts may contain significant sentiment orientation for institutions to incorporate changes to improve their course quality, teaching strategies, and other academic elements [6].…”
Section: Introductionmentioning
confidence: 99%
“…The experimental results on the real-life moods posts demonstrated that their methodology outperformed conventional multi-view semi-supervised emotion recognition methods. With the same intention, but under the ontology perspective, Gil, Virgili-Gomá, García, and Mason (2015) applied ontologies in the context of Emotional Common Sense, collaboratively collecting emotion common sense and modelling it with an ontology named EmotionsOnto. Their experiments were conducted to automatically measure users' emotional states using Brain Computer Interfaces.…”
Section: Related Workmentioning
confidence: 99%